Osimertinib treatment for patients with EGFR exon 20 mutation positive non-small cell lung cancer. (March 2020) - van Veggel, B.; Madeira R Santos, J.F. Vilacha; Hashemi, S.M.S.; Paats, M.S.; Monkhorst, K.; Heideman, D.A.M.; Groves, M.; Radonic, T.; Smit, E.F.; Schuuring, E.; van der Wekken, A.J.; de Langen, A.J.
Highlights: Limited antitumor activity of osimertinib in EGFR exon 20 mutated lung cancer. Objective response rate was 5 %. Median progression free survival was 3.6 months. A subgroup derived durable disease stabilization of five months and beyond. Abstract: Objectives: Epidermal growth factor receptor ( EGFR ) exon 20 insertions comprise 4–10 % of EGFR mutations in non-small cell lung cancer (NSCLC) and are associated with primary resistance to first and second generation EGFR tyrosine kinase inhibitors (TKIs). In vitro and preclinical animal studies have shown that osimertinib exerts antitumor activity against EGFR exon 20 mutation positive NSCLC. We report on a cohort of advanced stage NSCLC patients who harbor an EGFR exon 20 mutation and received osimertinib treatment. Material and methods: Twenty-one patients were treated with osimertinib 80 or 160 mg once daily from April 2016 to June 2018, in four institutions in the Netherlands. Data were obtained retrospectively. Progression free survival (PFS), disease control rate (DCR), overall survival (OS) and objective response rate (ORR) were assessed using RECIST v1.1. Results: Thirteen patients received prior platinum-based chemotherapy, and three patients a first – or second generation EGFR TKI. We observed 1 partial response, 17 patients with stable disease and 3 with progressive disease as best response to osimertinib (ORR 5 %). Median PFS was 3.6 (95 % CI, 2.6–4.5) months. PFS did not differ for patients with co-occurring TP53 mutations (p = 0.937). The DCR at three months was 71 %. Median OS was 8.7 (95 % CI, 1.1–16.4) months. Conclusion: Osimertinib has limited antitumor activity in patients with EGFR exon 20 mutated NSCLC, with an ORR of 5 %.